Problem Based Learning Model With Crt Approach in Improving Motivation and History Learning Outcomes on National and Regional Figure Material (Class Action Research Study in Class XII IPS SMAN 3 Medan) - Gaol, Vetty Lumban; Nugraha, Muhammad Adika; Sihotang, Masniar (LPPPI Publishing, 2024)
The aim of this research is to encourage student learning outcomes. This research is included in classroom action research in 2 learning cycles which are followed up in 2 meetings. In the first cycle, design, implementation, observation and improvement activities are carried out. The subjects of this research were 36 students in class XII IPS 1 SMA Negeri 3 Medan. Data collection is carried out using questionnaires, observations, and assessments or evaluations. Data processed and analyzed based on research that has been carried out illustrates that students experience progress in their learning outcomes, if learning indicators and the learning process are carried out using interesting methods. The students' learning outcomes in cycle 1 obtained an average score of 82.55 with a completion rate of 75%, while learning activities in cycle 2 achieved an average score of 92.25 with a completion rate of 88.25%. Through this achievement, the implementation of the CRT approach to learning activities can be a solution in encouraging student learning outcomes.